Collaborative Models as a Strategy for Strengthening the Economic Development of Indonesian Islamic Boarding Schools - Syaiful Anam; Mutia Pamikatsih; R Suhaimi; Bulkini Sasu (Ta'amul: Journal of Islamic Economics, 2026)
Collaboration is part of many companies' strategic alliances. Collaboration offers opportunities to leverage external capabilities and develop routines that can further enhance competitive advantage. Cooperation is an effective strategic tool to promote sustainable development. This research aims to conduct a literature review regarding the exploration of the concept of collaboration in Islamic boarding school economics. The research method used in this work is the SLR (Systematic Literature Review) method. Data collection is carried out by documenting all articles that have similar research in a research report. This research used 16 national journal articles taken from the Google Scholar database. Based on this research, it was found that the concept of collaboration in the economic sector has been widely discussed in several economic sectors. Such as tourism, MSMEs, economic recovery, business, financial institutions and cooperatives, economic education. Meanwhile, in the economic context of Islamic boarding schools, one article was found, namely about the implementation of the collaboration concept at the Darul Quran Mulia Islamic boarding school using a collaboration model with PT. Blessing Group. The use of collaboration in the economic system, especially the Islamic boarding school economy, can be developed as a strategic consideration for the Islamic boarding school economy in the future.